Health Policy and Maternal Mortality in Rwanda: A Case of Rwamagana District Hospital - Gad, Habarurema Samuel; Ngarambe, Prudence; Safari, Ernest (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2020)
The purpose of the study was to investigate the impact of health policy on maternal mortality in Rwanda, Rwamagana Hospital. The objectives of the study were: to investigate the impact of health policy on maternal mortality in Rwanda specifically Rwamagana Hospital, to examine the effect of medical insurance on maternal mortality rates in Rwanda - Rwamagana Hospital, to find out the influence of training of medical staff on the maternal mortality rate in Rwanda - Rwamagana Hospital, to find out the influence of mass immunization on maternal mortality rates in Rwanda especially in Rwamagana Hospital. The literatures were reviewed from different scholars and academicians in relation to the research study and the conceptual framework was based on three variables including independent variable shown as health policy and it was measured in terms of medical insurance, training medical personnel, and mass immunization, another variable was dependent variable shown as maternal mortality and it was measured in terms of malnutrition, disease, poor health services and poor antenatal care and another variable was the intervening variables that can falsify the findings of the study which includes building medical facilities, provision of medical care, educating women especially on human reproduction matters and hygiene and sanitation as well. The target population comprised 120 people and sample size of 92 respondents was considered using Yamane formula and purposive sampling technique was used. Questionnaires, documentary data and data analysis were expected to be used through SSPS version 21.0 while coding and cleaning the data collected from the field. The findings indicated that health policy has impact on maternal mortality in all health sectors of Rwamagana Hospital; for instance the results have indicated that health insurance is owned at rate of 91 (98.9%), easy access to medication at rate of 6 (6.5%), financial risk protection through protecting the resources spent on nursing sick children and maternal deaths at rate of 11 (12.0%), building of medical infrastructures and facilities at rate of 61 (66.3%). The findings also indicated there is correlation between health policy measure and maternal mortality prove that all the variables are positively significant at p-value under 0.05, despite that all the variables in correlation with poor antennal care gave negative Pearson correlation implied that the betterment of health policy decreases maternal mortality and recommendations were drawn basing on the study findings and challenges faced by Health policy beneficiaries whereby recommendations were addressed to medical personnel, government of Rwanda mainly ministry of health, local leaders, and expectant mothers and hence suggestions for further studies in line with Health policy were advised by the researcher as the study got its progress.